Do biological assemblages and ensembles really exist? - Monge-Nájera, Julián (2015)
In recent years the terms assemblage and ensemble have become more frequent in the ecological literature. After analyzing the definitions of the words in the French original, as well as their use in English and Spanish and opinions on how they can be defined, I conclude that the words assemblage and ensemble rarely improve scientific communication and can be eliminated from most ecological articles. The few justified exceptions are articles in which the emphasis is on how taxonomically close species interact trophically.